2021
DOI: 10.1002/app.50684
|View full text |Cite
|
Sign up to set email alerts
|

Torrefied agro‐industrial residue as filler in natural rubber compounds

Abstract: This study explored the feasibility of using torrefied biomass as a reinforcing filler in natural rubber compounds. Carbon black was then replaced with the torrefied biomass in elastomer formulations for concentrations varying from 0% to 100% (60 parts per hundred rubber or phr total). Their influence on the curing process, dynamic properties, and mechanical properties was investigated. Results were compared with the properties of vulcanizates containing solely carbon black fillers. Time to cure (t90) for comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 28 publications
4
25
0
Order By: Relevance
“…The rice hulls were torrefied and analyzed using methods described in a previous study. 11 Briefly, torrefaction of rice hulls was accomplished by placing 300 g of rice hulls in a 2 L steel vessel, which was then placed inside a Thermo Fisher (Waltham, MA) muffle furnace. The chamber of the furnace was flushed with nitrogen gas at a flow rate of approximately 2 L min À1 for 30 min to prevent combustion of the biomass during the heating process.…”
Section: Rice Hull Torrefactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rice hulls were torrefied and analyzed using methods described in a previous study. 11 Briefly, torrefaction of rice hulls was accomplished by placing 300 g of rice hulls in a 2 L steel vessel, which was then placed inside a Thermo Fisher (Waltham, MA) muffle furnace. The chamber of the furnace was flushed with nitrogen gas at a flow rate of approximately 2 L min À1 for 30 min to prevent combustion of the biomass during the heating process.…”
Section: Rice Hull Torrefactionmentioning
confidence: 99%
“…12 Upon torrefaction, the biomass was converted into a porous, carbonized solid, removing the water and partially decomposing the weak structural components, such as hemicellulose and, to an extent, cellulose. Increased hydrophobicity and microporosity (10-100 μm) 11 of the torrefied biomass improved filler interfacial adhesion with the NR matrix.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the modulus of TRH rubber composite showed the lowest modulus at 40:20 ratio before increasing gradually at 30:30 and 20:40 ratio. [ 25 ] Horsetail ( Equisetum Arvense ) Horsetail filler loading (10, 20, 30, 40 50 phr) Elongation at Break The elongation at break increases with increasing horsetail loading from 10 phr to 50 phr. Tensile Strength Tensile strength of rubber composite reinforced with horsetail show higher value than the pure natural rubber sample.…”
Section: Conventional Fillers For Natural Rubber Nanocompositementioning
confidence: 99%
“…Torres et al [ 25 ] and Moonart and Utara [ 28 ] concluded that the curing time increased consistently with increasing filler loading. The increase in curing time suggested that a retardation effect occurred during the curing process.…”
Section: Conventional Fillers For Natural Rubber Nanocompositementioning
confidence: 99%
See 1 more Smart Citation